Vulnerabilities of Indonesia’s Extractive Industry to Illicit Financial Flows - Oley, Jimmy Daniel Berlianto; Adi, Yerikho Setyo (Integritas : Jurnal Antikorupsi, 2018)
This article aims to explain the vulnerabilities of Indonesia’s extractive industry governance to the illicit financial flows. Earlier studies figured out that the company in extractive industry has been found to be one of the prominent actors of illicit financial flows. In the case of Indonesia during the period of 2004-2013, the data of Global Financial Integrity (GFI) illustrated that Indonesia is among the top 10 developing countries – which have the highest value of illicit financial flows. This article seeks to explain the nature of illicit financial flows on extractive industry, the causation of why Indonesia’s extractive industry is prone to the illicit financial flows, and finally the recommendation in addressing the issue. In doing so, the researchers conduct the qualitative desk research on explanatory methodology. The result explains that at least there are two natures of illicit financial flows on extractive industry, the behavior of rent-seeking and the dynamics of commodity prices. This article also found out that there are three main sources of regulatory vulnerability which may accommodate the rent-seeking behavior – which directly and indirectly influence the illicit financial flow, which are the different sets of revenue data, arm’s length measurement within the vulnerable enforcement, and regarding the cost recovery scheme. Other than that, the multi-level governance context shown by the decentralization policy of natural resources in Indonesia widens the loopholes of Indonesia’s extractive industry illicit financial flows.